Influence of pressure and sunflower husks ash as catalyst on tire-char steam gasification - Katarzyna Śpiewak; Piotr Soprych; Grzegorz Czerski (Energy Reports, 2023)
Catalytic gasification of low-reactive waste fuels, like tire-char, with the use of a different type of waste as a cheap and efficient catalyst seems to be an up-and-coming solution; however, requiring selecting appropriate process conditions. Therefore, this study aimed to assess the effect of various amounts (0, 5, 10, 15 wt%) of waste-based catalyst (sunflower husks ash, SHA) and pressure on tire-char gasification with steam. Feedstock and catalyst were characterised, then physically mixed, and the prepared samples were subjected to steam gasification. The gasification measurements were performed at 800, 850, 900 and 1000 °C and the pressures of 0.5 and 1 MPa, using the thermovolumetric method based on an analysis of the composition of the resulting gas (this research focused on the main gas components, i.e. CO and H2). The obtained results showed that the selected tire-char was characterised by a high calorific value; however, it contained a high content of carbon and catalytically inert ash, which may affect its reactivity. In turn, sunflower husk ash selected as catalyst consisted mainly of catalytically active compounds of alkali and alkaline earth metals (in particular K2O), while at the same time a low content of acid components that inhibit the process. The gasification measurements proved that the character of curves of formation rates of CO and H2differed, indicating different formation mechanisms. Moreover, pressure and catalyst addition affected the gasification process, especially at low temperatures (∼800–850 °C). In this temperature range, an increase in pressure, catalyst addition, and increasing its loading improved the conversion reaction rate and maximum carbon conversion, as well as hydrogen yields. In turn, an increase in pressure and the addition of catalyst positively affected the yield of carbon monoxide in almost the entire range of analysed temperatures, whereas the effect of catalyst was not significant. Finally, the analysis of kinetic parameters of carbon conversion reaction during steam gasification showed that the addition of catalyst reduced both activation energy and pre-exponential factor (the most significant reduction was observed when using 5 wt% of SHA), while the increase in pressure had an inverse effect on these parameters. Nevertheless, the obtained results show that steam gasification of tire-char at low temperatures, the pressure of 1 MPa and in the presence of 15 wt% of SHA may be an attractive way to efficiently obtain gas rich in hydrogen — one of the most promising future fuels.